President Juan Orlando Hernández's discursive fallacies in his brother Antonio “Tony” Hernández's drug court trial (Revista revoluciones, 2021)
Tony Hernández's judgment is probably the most important moment in Honduran political history, as it is the first time a Honduran politician has been prosecuted. Moreover, with this judgment it shows all the corruption that afflicts the institutionality of that country: the own brother of the President of the nation was prosecuted and found guilty of drug trafficking, whether organized crime reached the deepest state as the Executive Power. The study, through Critical Discourse Analysis, addresses the discursive ways in which President Hernández tried to defend himself and even justify his brother's judgment.